Political and Constitutional Thought Sami FrashÃ«ri - Sherifi, Elmaz (Richtmann Publishing, 2012)
Sami FrashÃ«ri is one of the most erudite Albanian minds of XIX century Albania. Born in Frasher, Permet on June 1st, 1850,Sami, an Ottoman citizen, stated